Indirect Virus Transmission in Cluster of COVID-19 Cases, Wenzhou, China, 2020 - Cai, Jing; Sun, Wenjie; Huang, Jianping; Gamber, Michelle; Wu, Jing; He, Guiqing (Emerging infectious diseases, 2020)
To determine possible modes of virus transmission, we investigated a cluster of coronavirus disease cases associated with a shopping mall in Wenzhou, China. Data indicated that indirect transmission of the causative virus occurred, perhaps resulting from virus contamination of common objects, virus aerosolization in a confined space, or spread from asymptomatic infected persons.